Design of Bioretention Planters for Stormwater Flow control and removal of Toxic Metals and Organic Contaminats. - Cuaran Bermudez, Andres Felipe; Lundberg, Linnea (My University, 2015)
In this project a bioretention planter (BP) that retain stormwater and reduce nickel (Ni), copper (Cu), zinc (Zn) and polycyclic aromatic hydrocarbons (PAHs) is designed for use in Gothenburg. Initially the research question was defined following the Challenge Lab process. As the maximum capacity is reached at the wastewater treatment plant (WWTP) in Gothenburg, stormwater has to be bypassed the treatment plant at heavy rains, and sustainable solutions to treat the stormwater closer to the source is needed. Green infrastructure, where water infiltrate in green areas, was identified as a solution to the stormwater over-flow pipe problems, but it gives a new environmental concerns when the contaminants accumulate in the soil. A combination of BPs and phytoremediation, a technology where plants are used to treat polluted soils, is a solution where both problems can be addressed. In addition to literature and design manuals of BPs, interviews has been carried out with stakeholders in the city. The result show that a BP with the depth of 1.5 m and surface area of 14.2 m2 can treat a volume of 9.5 m3 that is equivalent to water from an area of 200 m2 with a 50 mm rain in 24 hours. Suitable plants for treatment of Cu, Ni, Zn and PAHs are Populus deltoides x populus nigra L. (poplar), Salix (willow), Helianthus annuus (sunflower), Secale cereale L. (winter rye) and Medicago sativa (alfalfa). If the whole planter was filled with sunflowers, 154 mg of copper could be accumulated in the plant tissue per year, but in order to remediate PAH as well some space would have to be left for other plants. The cost to treat stormwater in BPs is calculated to 3.5 SEK per cubic meter, which is cheaper than the WWTP with a cost of 5.6 SEK per cubic meter. The Challenge Lab group process also included defining sustainability criteria for nature, society, economy and well-being, and the evaluation of the BP according to these criteria show that the solution is more sustainable than most alternatives.
Keywords: Energi; Hållbar utveckling; Miljövetenskap; Energy; Sustainable Development; Environmental Sciences